Challenges and Strategies on the Content and Language Integrated Learning Approach (CLIL): A Case Study from the Turkish Context - Akın Metlí; Dinçer Akıs (Universidad de La Sabana, 2022)
Limited studies investigate the high school teachers' challenges and strategies while teaching science and mathematics in English as the target language through the content and language integrated learning (CLIL) approach. Hence, this study aimed to investigate the challenges that science and math teachers encounter and the strategies they employ while fostering students' development of proficiency in English as the target language in physics, chemistry, biology, and mathematics courses in the International General Certificate of Secondary Education (IGCSE) and International Baccalaureate Diploma Program (IBDP). The study utilized various qualitative tools such as semi-structured interviews, open-ended questionnaires, and lesson observations to analyze science and math teachers' strategies and challenges at a case school in eastern Turkey. The study revealed that as part of the CLIL approach, the participant teachers indicated various challenges such as a lack of vocabulary repertoire, translation problems, and weak foundational knowledge. They used common strategies such as group work interactions, interdisciplinary activities, individualized feedback, the promotion of higher-order thinking skills, inquiry-based learning, and reinforcement of language used to deal with these challenges. The study presents further implications for good practices and recommendations to resolve challenges.